Tratamento eletroquímico de efluentes orgânicos integrado à produção de hidrogênio verde: Uma avaliação de viabilidade econômica - Arnosti, Gabriel Speranza (Universidade Federal de São Carlos, 2025)
Electrochemical oxidation is a promising technology for the treatment of organic effluents that are recalcitrant to biological treatment, utilizing electric energy to completely oxidize organic pollutants in wastewater, converting them into carbon dioxide at the anode of an electrolytic cell. The cell uses a boron-doped diamond (BDD) anode due to its high capacity to oxidize organic compounds, and a stainless steel cathode, separated by a membrane that ensures the production of pure hydrogen. The hydrogen produced using renewable energy in electrolysis is classified as green, and its commercialization reduces treatment expenses, making the process economically viable and environmentally beneficial without using chemicals to reduce the Chemical Oxygen Demand (COD) of the effluent. This study analyzes the economic feasibility of this process, whose batch model includes an electrochemical reactor and complementary equipment. Kinetic modeling, already consolidated in the literature with excellent agreement between experimental data and predicted values, is applied to analyze different initial COD values and current densities, evaluating the efficiency of electrochemical treatment and hydrogen production. The analysis highlights the financial benefits of the treatment and its contribution to sustainable practices in green hydrogen production. Through the Cost-Benefit Index (CBI), the ratio of profit from gas commercialization to electricity cost, the most economically attractive condition was defined. A CBI of 0.63 was obtained for a current density of 100 A m⁻², this value being independent of the analyzed initial COD values. The impact of the process's operational and capital expenses was evaluated to identify the ideal economic condition, concluding with the financial analysis of the investment in terms of Payback and Net Present Value (NPV). It was found that low current densities maximize cost recovery, as they result in lower OPEX for the process and allow for higher profit margins. In this scenario, despite significantly higher CAPEX due to the increased anodic area requirement, it was estimated that with a high-profit margin, the payback was 3 years and the NPV for an 8-year period reached US$ 1,041,127, suggesting the economic feasibility and attractiveness of the investment.
Electrochemical treatment of organic wastewater integrated with green hydrogen production: An economic feasibility assessment
Keywords: Oxidação eletroquímica; Efluentes orgânicos; Hidrogênio verde; Análise econômica; Demanda química de oxigênio; ENGENHARIAS::ENGENHARIA QUIMICA